Correlation of Cerebral Metabolites with Functional Outcome in Experimental Primate Stroke Using in Vivo 1H-Magnetic Resonance Spectroscopy - Coon, A.L.; Arias-Mendoza, F.; Colby, G.P.; Cruz-Lobo, J.; Mocco, J.; Mack, W.J.; Komotar, R.J.; Brown, T.R.; Connolly, E.S. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Ensuring the translatability of primate stroke models is critical for preclinical testing of cerebroprotective strategies, and such models would benefit from further characterization of the experimental ischemic tissue. Our purpose was to examine the cerebral metabolic response to stroke in baboons with MR spectroscopy and to correlate metabolite levels with functional neurologic outcomes.METHODS: Seven baboons underwent 1 hour of middle cerebral artery occlusion. At 3 and 10 days, each animal was imaged with traditional MR imaging and multivoxel proton 1H-MR spectroscopy, and a neurologic examination was performed. Spectra obtained from the infarcted hemisphere of each animal were compared with the contralateral hemisphere, and metabolite levels were correlated with neurologic outcome scores.RESULTS: Spectra obtained at 3 days postischemia revealed prominent lactate (LAC) resonances and attenuated N-acetylaspartate (NAA) peaks in infarcted hemispheres. Ten-day spectra showed persistence of these findings in animals with large strokes (>30% of the hemisphere), with partial normalization of the spectra in animals with small strokes (<30% of the hemisphere). Mean area under the curve from LAC spectra had a negative correlation with functional outcome by 2 different scoring systems (r2 = 0.72 and 0.73), whereas NAA showed a positive correlation (r2 = 0.79 and 0.62).CONCLUSIONS: The metabolic alterations observed in our primate model of reperfused ischemia by 1H-MR spectroscopy recapitulate those seen in clinical stroke. Furthermore, correlations between LAC and NAA peaks with functional outcome further suggest that MR spectroscopy may play a role in outcome prediction following cerebral infarction in higher primates.